SISTEM KONEKSI X – BEE SEBAGAI KENDALI JARAK UNTUK PENGELOMPOKAN BUAH KOPI MENGGUNAKAN SENSOR TCS 3200 - Sarjana Sarjana; Emilia Hesti (Politeknik Sekayu, 2018)
Lots of inventions as well as all the uses of technological advances that are very helpful in alleviating humanwork, especially in the field of industry that cultivate fruit crops with small size.This paper provides a method of accelerating use of TCS3200 color sensors for color quantization, it was donewith various images and showed that the modifications have been able to show that the TCS3200 color sensor isalso very competitive as the color quantization of images, both in terms of effectiveness and efficiency.On the other hand, this system will use the pattern by knowing the coffee grouping control system with wirelesssignal using Xbee pro module, where the XBee Proo module is to set the remote control with wireless networkassisted, so the farmers do not have to bother to controling from close range. Furthermore, the data base will bebuilt for several colors of fruit coffee and the comparison of fruit shape to be made with a control systemgrouping the fruit of coffee will be done using servo motors, so that when the tool works will be in line with theuse of color sensors that can detect the color of the coffee beans.